Continuous labor support program on the importance and application of supportive behaviors in midwifery students - Fatemeh Bakouei; Maryam Nikpour; Fereshteh Behmanesh; Golnar Nasehi (Babol University of Medical Sciences, 2017)
BACKGROUND AND OBJECTIVE: Continuous labor support for pregnant mothers is effective in reducing pain and anxiety. Factors that may increase the cesarean sections and decline the fertility. This study aimed to evaluate the clinical education of continuous labor support to midwifery students in the importance and use of supportive behaviors by students. METHODS: In this quasi-experimental study, 34 midwifery students were selected through census sampling. Students in groups of 7-5 members, practically trained the continuous labor support techniques by midwifery clinical teachers in the clinical setting. To determine the impact of the intervention, the Labor Support Questionnaire (LSQ) was used before and after the intervention. Data analysis was performed using SPSS software v.23 and descriptive statistics, t-test and linear regression. A worth of significantly less than 0.05 was considered significant. FINDINGS: According to the study findings, continuous labor support education to the midwifery students at the clinical setting, has been led to a significant increase in the rate of importance and application of supportive labor practices in four areas of physical, emotional, advocacy and information. In linear regression analysis, none of the variables studied had significant relationship with the importance and the use of supportive behaviors. CONCLUSION: With regard to the impact of clinical education to the importance and application of labor support methods on midwifery students, it is necessary to the students become familiar with the supporting models and attempt to do it until after graduating, they can use these methods as a staff.